Health education in the context of aging: in focus, the curricular contents (Research, Society and Development, 2018)
The present study has the objective of analyzing the approach of the aging theme in the training of professionals of higher education that integrate the Family Health Strategy (FHS) and the Family Health Support Center (NASF) teams. This is a study with a qualitative approach, of the document type, carried out in the state of Rio Grande do Norte, Brazil. In order to reach the objective, the pedagogical projects of the courses for the mentioned professions were analyzed, based on the content analysis method, using the thematic analysis technique in three pre-established registration units: (i) skills and abilities ; (ii) professional profile; and (iii) curricular structure. As part of the results, from the operationalization of the analysis of the pedagogical projects emerged two thematic categories: Discussion on aging and training for health care of the elderly. The study shows that the discussion about aging in the training process of higher education professionals that integrate the FHS and NASF teams is still incipient. Thus, it is necessary to prepare people to offer integral attention to the elderly population, as well as to formulate and manage public policies for the mentioned user population of the Unified Health System (SUS).